PERAN GURU PAI DALAM MENGATASI PEMBULIAN MELALUI INTERNALISASI NILAI-NILAI AKHLAKUL KARIMAH DI SMP NOER HIDAYAH BEKASI - Syakyla, Azzahra Desiyanti; Maulidin, Syarif; Kurniawan, Wakib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is a process of forming civilized human beings that is not only oriented toward the mastery of knowledge, but also toward the development of students’ values, morals, and character. As an educational environment, school should provide a safe, comfortable, and conducive space for students’ development. However, the reality in the field shows that bullying remains a problem that can affect students’ psychological, social, and academic development. This study aims to examine the role of Islamic Education teachers in overcoming bullying through the internalization of akhlakul karimah values at SMP Noer Hidayah Bekasi, the strategies used, and the obstacles encountered in its implementation. This study employed a qualitative approach with a descriptive research type and a case study design. The data were collected through semi-structured interviews, observation, and documentation. The research informants consisted of the principal, Islamic Education teacher, guidance and counseling teacher, students, and students’ parents. Data analysis was carried out through data reduction, data display, conclusion drawing, and verification. Data validity was ensured through source triangulation and member checking. The results of the study show that the role of the Islamic Education teacher in overcoming bullying is more dominant in the aspects of prevention and moral development. The Islamic Education teacher acts as an educator, mentor, role model, religious value reinforcer, and collaborator with school elements and parents. The strategies used include integrating moral values into Islamic Education learning, giving advice, providing exemplary behavior, habituating polite conduct, conducting religious activities, and collaborating with related parties. The obstacles encountered include differences in educational patterns between school and home, peer influence, gadget and social media use, limited learning time, and the less-than-optimal cooperation of parents. This study concludes that the internalization of akhlakul karimah values is an important effort to prevent and reduce bullying by developing students’ attitudes of mutual respect, careful speech, empathy, and responsibility.